Engenheiros e fazendeiros em uma ferrovia de capitais caipiras: a Estrada de Ferro Araraquara e os contornos da grande empresa de serviços públicos na primeira república - Silva, Henry Marcelo Martins; Tosi, Pedro Geraldo Saadi [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2020)
This research aims at analyzing the action of farmers and engineers in the history of the Araraquara Railroad (Estrada de Ferro Araraquara), a railway that linked the city of Araraquara to the western backwoods of São Paulo in the early 20th century, São José do Rio Preto. The company, founded in 1896 with essentially local capital during a period of difficulties for the groups linked to the coffee production complex, had a short and tumultuous life as a private company, being object of diverse interests in an environment of great economic speculation. In that context, the actions of a group of engineers stand our; by taking over the control of shares, they promoted a calamitous administration, taking huge loans at home and abroad, which lead to bankruptcy and later expropriation of the company by the State in 1919, in a turbulent process involving large investors from Brazil and Europe. Based on sources such as the Relatórios de Exercícios (E. F. Araraquara Exercises Reports) and several newspapers of that time, this paper intends to understand the difficulties of the railway trajectory, the transformation in the profile of the shareholders, as well as the conditions that enabled the group of engineers to take control and lead the company to bankruptcy, a process permeated by strategies and negotiations that elucidate the contours of the large utility company in the First Republic.

Esta pesquisa busca compreender a ação de fazendeiros e engenheiros na trajetória da Estrada de Ferro Araraquara, linha férrea que ligava a cidade de Araraquara à boca do sertão oeste de São Paulo no início do Século XX, São José do Rio Preto. A companhia, fundada em 1896 com capitais essencialmente locais em um período de dificuldades para os segmentos ligados ao complexo cafeeiro, teve uma curta e tumultuada vida como empresa privada, sendo objeto de interesses diversos em um ambiente de grande especulação econômica. Nesse contexto, destaca-se a atuação de um grupo de engenheiros que, tomando o controle acionário, promovem uma administração calamitosa, contraindo empréstimos de grande monta no país e no exterior, que culminou na falência e posterior encampação da companhia pelo Estado em 1919, num processo conturbado que envolveu grandes investidores do país e da Europa. A partir de fontes tais como os Relatórios de Exercícios da E. F. Araraquara e diversos jornais do período, o trabalho pretende compreender as vicissitudes da trajetória da ferrovia, a transformação no perfil dos acionistas, bem como as condições que permitiram a ação do grupo de engenheiros no controle e falência da companhia, processo permeado de estratégias e negociatas que elucidam os contornos da grande empresa de serviços públicos na Primeira República.
Engineers and Farmers in a Railroad of Caipira Capitals: The Araraquara Railroad and The Contours of The Great Public Service Company in The First Republic
Keywords: Farmers; Railway Capital; Engineers; Capital Market.; Fazendeiros; capital ferroviário; engenheiros; mercado de capitais.